Best Answer

Collect all the letters on one side and the numbers on the other; what you do to one side of the equals you do to the other:

3z + 2 = 6z - 13

→ 3z +2 - 3z = 6z - 13 - 3z

→ 2 = 3z - 13

→ 2 + 13 = 3z - 13 + 13

→ 15 = 3z

→ 3z = 15 (this is just changing the equals around so that the letter is on the left)

→ 3z ÷ 3 = 15 ÷ 5

→ z = 5

🙏

🤨

😮

Study guides

☆☆

Q: How do you solve 3z plus 2 equals 6z minos 13?

Write your answer...

Submit

Still have questions?

Related questions

5

X +13 equals 22, X equals nine

12 + 5 equals...

To solve for x, we'd have to know what this expression equals.

If: 2a+13 = 5a+1 Then: a = 4

7+6

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

(x - 3)(x + 5)

6+8=14

13=e+2 11=e (subtract 2 from each side)

6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6

3h+13 = 7 3h = 7-13 3h = -6 h = -2

6x-2=x+135x=15x=3

+6

5

9=4a+13 9-13=4a -4=4a -4/4=a -1=a a=-1

13+13=26

It cannot because neither statement is true.

x-29 = 13+2x x-2x = 13+29 -x = 42 x = -42

9a + 4a = 26 13a = 26 a = 26/13 a = 2

16

273 13+8 = 21 and 13*21 = 273

4r + 13 = 57subtract 13 from both sides:4r + 13 - 13 = 57 -134r = 44divide both sides by 4 to solve for r:4r/4 = 44/4r = 11

If -3q + 4 = 13 then 3q = -9 : q = -3 If 6q = 13 then q = 13/6 = 2 1/6 The question contains an anomaly and is invalid.

yes it is